Efek Pemberian Kompos dan Biochar terhadap Pertumbuhan Bawang Merah (Allium ascalonicum L.) True Shallot Seed Pada Typic Hapludults - Ajeng Siwi Nuraini; Putra Utama; Abdul Hasyim Sodiq (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2022)
The research was aimed to determine the growth of shallot (Allium ascalonicum L.) from true shallot seed (TSS) by giving compost and biochar in Typic Hapludults soil. This research was conducted at the Greenhouse and Laboratory of Soil and Agroclimate, Agriculture Faculty, Sultan Ageng Tirtayasa University and conducted on November 2020 to January 2021. This research used a factorial randomized block design (RBD) consisted of two factors, that were compost and biochar dosage that mixed into the suboptimal soil. The first factor was the dosage of compost (K) which consisted of 3 levels, that were 12.5 tonnes/ha (k1), 25 tonnes/ha (k2), and 37.5 tonnes/ha (k3). The second factor was the dosage of biochar (B) which consisted of 3 levels of experiment, namely 7.5 tonnes/ha (b1), 10 tonnes/ha (b2), and 12.5 tonnes/ha (b3). The results showed there was no interaction between the application of compost and biochar to suboptimal soil on the growth and yield of shallot. Giving biochar of 7.5 tonnes/ha had a significant effect on the parameters of the number of leaves at 1 WAP.